2009
DOI: 10.3758/app.71.6.1251
|View full text |Cite
|
Sign up to set email alerts
|

Spatial asymmetries in viewing and remembering scenes: Consequences of an attentional bias?

Abstract: Given a single fixation, memory for scenes containing salient objects near both the left and right view boundaries exhibited a rightward bias in boundary extension (Experiment 1). On each trial, a 500-msec picture and 2.5-sec mask were followed by a boundary adjustment task. Observers extended boundaries 5% more on the right than on the left. Might this reflect an asymmetric distribution of attention? In Experiments 2A and 2B, free viewing of pictures revealed that first saccades were more often leftward (62%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 79 publications
8
71
1
2
Order By: Relevance
“…Other factors that have been suggested to contribute to the central bias are the distribution of salient features or objects in the scene (photographer bias) or orbital reserve, and Tseng, Carmi, Cameron, Munoz, andItti (2009) andTatler (2007) have considered these factors in detail. There was also a slight leftward bias at the start of viewing, which is consistent with the results of Dickinson and Intraub (2009), who recently reported a leftward asymmetry in scene perception. The preference to move to the left side of the image was found across a range of scenes and, therefore, seems unlikely to be caused by an uneven distribution of features or objects within the scene (for further discussion of the role of image features in saccade asymmetries, see Foulsham & Kingstone, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Other factors that have been suggested to contribute to the central bias are the distribution of salient features or objects in the scene (photographer bias) or orbital reserve, and Tseng, Carmi, Cameron, Munoz, andItti (2009) andTatler (2007) have considered these factors in detail. There was also a slight leftward bias at the start of viewing, which is consistent with the results of Dickinson and Intraub (2009), who recently reported a leftward asymmetry in scene perception. The preference to move to the left side of the image was found across a range of scenes and, therefore, seems unlikely to be caused by an uneven distribution of features or objects within the scene (for further discussion of the role of image features in saccade asymmetries, see Foulsham & Kingstone, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…As it was demonstrated by Intraub et al (2006), BE can be affected by planned eye fixations: while BE appeared on the cued (to-be-fixated) side of the image, it was inhibited on the uncued side. Inconsistent with this finding, research demonstrated that focal and increased attention may constrain BE error (Dickinson & Intraub, 2009;Intraub, Daniel, Horowitz, & Wolfe, 2008). Overall, these findings implied that asymmetry in scene representation may be caused by the anticipatory processing in a certain direction.…”
Section: Introductionmentioning
confidence: 86%
“…It has indeed been shown that viewers have a leftward bias in starting scene inspection (Dickinson & Intraub, 2009;Foulsham & Kingstone, 2010;Nuthmann & Matthias, 2014;Ossandón, Onat & König, 2014). In the "original" (evaluated) orientation, two scenes had both objects in the left half, two had both objects in the right half, while the remaining had one object in each side.…”
Section: Methodsmentioning
confidence: 99%